Desenvolvimento e validação de métodos para a determinação de agrotóxicos em água e solo das áreas de recarga de Aquífero Guarani, na região das nascentes do Rio Araguaia, MT/GO. - MORAIS, L. S. R. de (2009)
Abstract: The area near the Araguaia River, between Goiás and Mato Grosso States, is the location of a portion of the recharging of the Guarani Aquifer, which is one of the world¿s largest aquifer systems and an important source of drinking water. This reservoir could be threatened by the widespread use of pesticides in maize and soybean cultivation in this area. Thus, this work developed analytical methods for the determination of imazethapyr, nicosulfuron, imazaquin, carbofuran, atrazine, linuron, clorimuronethyl and diflubenzuron, pesticides used in maize and soybean cultivation. Pesticide separation, identification and quantification were performed using High-Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD) and Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry (LC-ESI-MS/MS). Solid Phase Extraction (SPE) with C18 sorbents was optimized for sample extraction from water. Soil samples were extracted by mechanical shaking, sonication or microwave-assisted extraction with industrial and home microwave ovens. Methods were validated resulting in limits of quantification (LOQ) for the pesticides in water in the range of 0.015-0.1 ng mL, using SPE-HPLC-DAD, and 0.01 ng mL using LC-ESI-MS/MS. LOQ of 1 ng mL for all pesticides in soil were achieved using the home microwave oven and LC-ESI-MS/MS. Recoveries for pesticides with all methods were in the range 70-120 %. Relative standard deviations for repeatability and intermediate precision were less than 15 %. SPEHPLC- DAD and LC-ESI-MS/MS were employed for the analysis of samples of water from the recharge area and most of the pesticides were detected at concentrations below the minimum residue limit (MRL) of 0.1 ng mL established by the European Community. The home microwave oven and LC-ESI-MS/MS were used for the analysis of soil samples from two other regions of Brazil and the pesticides were not detected in these samples. Adsorption and desorption parameters were determined for imazethapyr, imazaquin, nicosulfuron and chlorimuron-ethyl, indicating that these pesticides have little affinity for the soil of the region of the Guarani Aquifer recharge, and show significant leaching potential, according to the ground water ubiquity score (GUS index) for these pesticides.